2022
DOI: 10.35912/ahrmr.v2i2.1418
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review on Human Resource Management Effect on Organization Performance

Abstract: Purpose: The current study is the outcome of a thorough evaluation of the literature on functionalism in human resource management as it relates to organizational performance. It examines the role of human resource management and looks into various issues with human resource management in firms in such situations. Research Methodology: The theoretical underpinnings are accomplished through a systematic review and subsequent thematic content analysis of literature, including reports from published literature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The study outcome further aligns with the conclusion of a study by Seliverstova, (2021), which explains that age diversity assists in the creation of an environment of work that mirrors a broader societal trend of an ageing workforce, thus promotes task performance. Finding from the study was found to correlate with the opinion of Adula et al, (2022) whose study provided that age diversity creates a platform towards empowering employees to contribute uniquely their perspectives and skills in the attainment of overall objective of their organisations.…”
Section: Discussion Of Findingsmentioning
confidence: 79%
See 1 more Smart Citation
“…The study outcome further aligns with the conclusion of a study by Seliverstova, (2021), which explains that age diversity assists in the creation of an environment of work that mirrors a broader societal trend of an ageing workforce, thus promotes task performance. Finding from the study was found to correlate with the opinion of Adula et al, (2022) whose study provided that age diversity creates a platform towards empowering employees to contribute uniquely their perspectives and skills in the attainment of overall objective of their organisations.…”
Section: Discussion Of Findingsmentioning
confidence: 79%
“…In addressing age diversity in the university workplace, it is essential to recognize that diversity goes beyond age, encompassing factors such as gender, ethnicity, and cultural background. Embracing a holistic approach to diversity and inclusion fosters an environment where all employees, regardless of age, feel empowered to contribute their unique skills and perspectives to the collective success of the institution (Adula et al, 2022).…”
Section: Age Diversitymentioning
confidence: 99%
“…A meta-analysis is a methodical approach for integrating quantitative results from several empirical researches that investigate how an independent variable (or intervention, or determinant, or treatment) impacts certain outcomes (or dependent variables) (Adula et al, 2023). In the social sciences, meta-analysis is becoming a more popular way to examine hypotheses.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the company may have the necessary technical infrastructure to enter into a smart contract, but because the legal infrastructure does not exist in the event of a dispute and a claim authority, the smart contract may not be effective in practice. Interoperability in the application of blockchain includes both technical and organizational, structural and inter-organizational dimensions (Adula, Kant, & Birbirsa, 2022;Anochiwa, 2021;Savelyev, 2017).…”
Section: Criteria For Assessing the Readiness To Accept Blockchain In...mentioning
confidence: 99%